Mens Violence Against Women the Need to Take Responsibility - Lorentzen, Jørgen; Løkke, Per Are (The Bulletin of Legal Medicine, 1998)
The problem of violence has become a central part of European politics and of each human being in the European countries. We have heard reports of massive rape rituals in Bosnia, we are witnessing a Belgium in deep sorrow because of the slaughter of its daughters, we are experiencing gang wars in the inner cities, In every country, racism is creating death and pain and fradually the knowledge of violence against women and children in their own homes is reaching our consciousness. Most of the time, this violence is talked about in the media in terms of gangsters, devils, murderers, bandits, drug addicts, blacks, nazis, rapists or just thieves, Very seldom are the perpetrators talked about as men, and almost never are they understood within the concept of masculinity. Even when the fact undoubtedly is that they are, in almost every case, men. One of the most important things is that we need to know more about how masculinity is created. What does it mean that the violators are men? What implications will this have for the understanding of violence? What is the specific relationship between masculinity and violence? And: How will it influence the politics of violence - the work against violence in the media, in the streets and in the society as a whole? These types of questions will be the guidelines of our talk here today. Let us go straight to the heart of the problem. While the media and the public's attention are concentrated on the violence which occurs in the public sphere, they are forgetting the violence in the private sphere. Our claim is that the violence which we see in public is largely rooted in the private sphere, It is violence carried out in the private sphere which is transferred and extended into the public sphere. In other words, it is the private violence which should claim our attention, and it is against this violence that the efforts to combat violence should be directed. Focusing on private violence will also enable us to bring to bear a clearer gender perspective. Even though we know that women use violence against men and children, private violence mainly consists of men's violence against those nearest to them: girlfriends, wives and children. Let us therefore spend the few minutes we have presenting three perspectives on men's violence against women, in order better to get to know these men.
Keywords: forensic meicine; violence against women